Fulfilling Physical Disable Base Right - Kuntjorowati, Elly (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The numbre of physical disabled coming from poor families are not fulfilled their basic rights, such as food, clothing, education, health and employment, showed an unqualified families in meeting their basic needs and attention to the disabled. The research aimed to find out the level of fulfillment of physical disabledbasic needs by their family. The type of research was descriptive, data collectedthrough interviews and observation techniques. The research location in Ogan Komering Ilir, South Sumatra Province. Data were analyzed through descriptive tehnique. The research showed that lack of social support from family, especially parents, to meet basic needs of disables such as nutrition, education, health and employment.It recomendedthat is requiredto hold empowerment for of disable’s parents to improve their knowledge and ability to care and gain access to existing social services programs.